Correspondence, power and the state : an historical geography of the Irish Postal Service, 1784-1831 - Prendiville, Garry (Trinity College (Dublin, Ireland). Department of Geography, 2006)
An Historical Geography of the Irish Postal Service, 1784-1831 Summary The aim of this thesis is to outHne an historical geography of the Irish postal service during the period of the late eighteenth and early nineteenth centuries. In order to do this the thesis charts the growth of the Post Office during this period by providing a narrative of the development of the postal network. The description of the network’s development revolves around three main axes; internal growth, external growth and structural change. The ‘story’ of Post Office growth during the period 1784-1831 is told under these three headings. That ‘story’ involves the examination of such issues as how mail was delivered, how many post offices there were and where they were situated, how fast the mail travelled, how efficient the system was, how much it cost to send a letter, the detailing of the transport links between Britain and Ireland and the depiction of how the Post Officer operated as a bureaucratic structure. It is in doing so that the thesis provides a solidly empirical basis for the reconstruction of the detail of how the postal service operated during this period.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin